EVALUASI KETERCAPAIAN TUJUAN PROGRAM BEASISWA BIDIKMISI MAHASISWA FT UNP - 485-492 , Dedy Novrijal (Universitas Negeri Padang, 2015)
Abstract This research is motivated from the persistence problem Bidikmisi students who obtained GPA below 2.75, so the scholarship Bidikmisi discontinued. One purpose of the scholarship Bidikmisi that ensure the sustainability of the student to complete the study.This study aims to determine the achievement of program objectives Bidikmisi scholarship students FT UNP.This research was conductedon the candidates Bidikmisi year in 2011 in the FT UNP. The number of samples in this study were 83 respondents. Types and sources of data are the primary data derived from questionnaires given to 83 respondent sand secondary data Bidikmisi year scholarship recipients entered 2011 FT UNP. Data collection techniques using a questionnaire with Likert scale, data analysis techniques using descriptive analysis.The results showed 73.11% of students study the sustainability of 65.14% and student achievement in academic and non-academic in the high category, it indicates that the purpose of the scholarship program is reached. But there are some who have not reached the goal, so the goal of the scholarship program Bidikmisi FT UNP student enrollment year 2011 has not been fully achieved. Keywords: Evaluation ofgoal achievement, scholarshipBidikmisi